2017
DOI: 10.3390/v9070172
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis Delta Virus: Replication Strategy and Upcoming Therapeutic Options for a Neglected Human Pathogen

Abstract: The human Hepatitis Delta Virus (HDV) is unique among all viral pathogens. Encoding only one protein (Hepatitis Delta Antigen; HDAg) within its viroid-like self-complementary RNA, HDV constitutes the smallest known virus in the animal kingdom. To disseminate in its host, HDV depends on a helper virus, the human Hepatitis B virus (HBV), which provides the envelope proteins required for HDV assembly. HDV affects an estimated 15–20 million out of the 240 million chronic HBV-carriers and disperses unequally in dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 132 publications
(164 reference statements)
0
31
0
3
Order By: Relevance
“…1, ▶ Table 2). The only viral factor that could be therapeutically addressed is the HDAg or the two ribozymes, which are essential for HDV RNA replication [77]. Unfortunately, no such antiviral drug has been developed so far.…”
Section: Towards Curative Therapy For Chronic Hepatitis Dmentioning
confidence: 99%
“…1, ▶ Table 2). The only viral factor that could be therapeutically addressed is the HDAg or the two ribozymes, which are essential for HDV RNA replication [77]. Unfortunately, no such antiviral drug has been developed so far.…”
Section: Towards Curative Therapy For Chronic Hepatitis Dmentioning
confidence: 99%
“…Blank et al 2 found that the concentration of Myr that blocks HDV entry is 100 times lower than that inhibiting bile acid transport. The drug is well tolerated with no dose limiting toxicity.…”
Section: Myrcludex Bmentioning
confidence: 99%
“…Although modest and transient increases of amylase and lipase occur, they are clinically uneventful and spontaneously resolved. Bogomolov et al 2 treated seven patients with Myr at a dose of 2 mg daily subcutaneously for 24 weeks. Therapy was accompanied by more than a 1 log 10 reduction in serum HDV RNA in four patients and by its clearance in two.…”
Section: Myrcludex Bmentioning
confidence: 99%
“…19 The HBsAg binds to the NTCP via the myristoylated Nterminal receptor site of the viral preS1 domain; 20 the binding is blocked in cell culture and in a humanized mouse model by synthetic lipopeptides that mimic the receptor site within the preS1 domain. [21][22][23] The first block-entry drug used in CHD is Myrcludex B (MyrB), a myristoylated synthetic N-acylated peptide of the preS1 domain of the HBV.…”
Section: New Drugs Targeting the Hdv Myrcludex Bmentioning
confidence: 99%
“…Further combination studies are currently in progress, with MyrB administered at three different doses (2-5-10 mg) together with tenofovir versus tenofovir alone for 24 weeks and together with IFN-α versus IFN-α alone for 48 weeks. 23 Studies in progress with LNF were also designed in combination with Peg IFN. In the LOWR HDV-2, patients are given low doses of LNF (75 mg, 50 mg or 25 mg twice a day) together with ritonavir, with or without Peg IFN for 12 to 24 weeks; 36 at week 24 of therapy, 25 mg LNF (plus 100 mg ritonavir) and Peg IFN had reduced serum HDV-RNA below the limit of quantification in five of five treated patients.…”
Section: Commentsmentioning
confidence: 99%